Pengaruh Model Pembelajaran SAVI (Somatis, Auditori, Visual, Intelektual) terhadap Keterampilan Menulis Teks Eksposisi Siswa Kelas X SMA N 14 Medan - Ayu Permatasari Sihotang; M. Joharis Lubis (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
One of the aims of this research is to identify students' writing skills taught by the Somatic, Auditory, Visual and Intellectual (SAVI) learning model in expository texts written by students in class X SMA N 14 Medan. Another aim is to find out how the problem-based learning model (PBL) and the SAVI (Somatic, Auditory, Visual and Intellectual) learning model have an impact on the exposition text. This research involved all students in class X SMA N 14 Medan, with a simple random sample, consisting of 36 students in class X-1 and 36 students in class X-2. A two-group post-test experimental method was used and the research instrument was an expository text writing test. The